Transcanalicular laser-assisted and external dacryocystorhinostomy anatomical and functional success in primary acquired nasolacrimal duct obstruction: systematic review and meta-analysis - Khalid W. Helmi; Ahmed S. Abdulhamid; Mohammed S. Alomari; Ali S. Alsudais; Badran S. Alqurashi; Abdullah Alsharif; Abdulrahman H. Alzahrani; Abdulrahman M. Bahalaq; Mohammed F. Qutub; Hashem S. Almarzouki (BMC Ophthalmology)
Abstract Background Primary acquired nasolacrimal duct obstruction (PANDO) is a condition in which tear ducts are blocked, leading to epiphora and dacryocystitis. This systematic review and meta-analysis aimed to measure the ability of transcanalicular dacryocystorhinostomy (TC-DCR) as an alternative approach to PANDO compared to traditional external dacryocystorhinostomy (EX-DCR). Methods Our search included Embase, Medline, and the Cochrane Central Register of Controlled Trials (CENTRAL). We included only observational studies, randomized controlled trials (RCTs), and quasi-experimental studies that compared TC-DCR and EX-DCR. The outcomes measured were anatomical and functional success rates, intraoperative complications, postoperative complications, and surgical time. Statistically significant results were determined as a p value of less than 0.05; thus, a confidence interval of 95% was used. Dichotomous outcomes were reported via risk ratios (RR), whereas continuous outcomes were reported using standardized mean differences (SMD). Results There was a statistically significant difference in anatomical success (RR = 0.84, 95% CI 0.72–0.97; P = 0.02), favoring EX-DCR; functional success (RR = 0.87, 95% CI 0.78–0.97; P = 0.01), favoring EX-DCR; operative (OR) time (SMD = -2.42, 95% CI -2.92 – -1.91; P < 0.00001) favoring TC-DCR; and intraoperative complications (RR = 0.16, 95% CI 0.06–0.43; P = 0.0003), favoring TC-DCR. Moreover, the subgroup analysis comparing single-diode TC-DCR to EX-DCR revealed a statistically significant difference in terms of anatomical success and functional success; however, the comparison of multidiode TC-DCR to EX-DCR revealed no statistically significant difference. Conclusions More research should be conducted to compare the anatomical and functional success of muli-diode TC-DCR with EX-DCR because the analysis performed comparing them revealed no statistical significance.